A study of the effect of water content change on the properties of foamed asphalt mixtures - سماحه محمد; بسام سلطان (Latakia University Journal -Engineering Sciences Series, 2023)
With the development and progress in the manufacture of bituminous mixtures, the reality of traditional bituminous mixtures must be developed, which results in the emission of polluting gases to the environment and the workers who implement these mixtures on site. However, their production leads to energy consumption because both bitumen and gravel need to be heated. The trend towards solutions to reduce these emissions and energy, and one of these solutions is the production of foamy bituminous mixtures made of foamed bitumen, which is characterized by two characteristics: the expansion ratio and the half-life, which include in its design several factors such as air pressure, water pressure, and the temperature of heating the bitumen to a degree Foaming and a small amount of water usually (2-4)% as a percentage of the bitumen content is added to the bitumen heated to the foaming temperature to become foamy and then mixed with the pebbles at the ambient temperature, where the proportion of water is the most influential in the production of these mixtures and thus In our research, we directed to study the effect of changing the water content inside its production on its stability and strength, as we foamed bitumen with variable water ratios from 2% to 4% with an increase of 0.1%, and thus we obtained an expansion ratio and a half-life. Marshall molds and testing them on stability and flow, and comparing them with traditional mixtures, where the results of the stability of the foamy bituminous mixtures at all water levels were greater than the stability of the hot bituminous mixtures, and thus this confirms that these mixtures give improved strength to the mixture, it was found that at a water percentage of 2.3% it gave the greatest stability For the foamy mixture of 1488 kg, it increased by 22.47% over the stability of the hot bituminous mixture, and the lowest value of flow was 2.6 mm. As for the air voids and filled voids in the design of the foamed bituminous mixtures, these mixtures improved by reducing the proportion of air voids and increasing the proportion of voids filled with bitumen.